PHANGS-JWST first results: measuring polycyclic aromatic hydrocarbon properties across the mltiphase iterstellar mdium - Chastenet, Jérémy; Sutter, Jessica; Sandstrom, Karin; Belfiore, Francesco; Egorov, Oleg; Larson, Kirsten L.; Leroy, Adam K.; Liu, Daizhong; Rosolowsky, Erik; Thilker, David A.; Watkins, Elizabeth J.; Williams, Thomas G.; et al. (The astrophysical journal. Part 2, Letters, 2023)
Ratios of polycyclic aromatic hydrocarbon (PAH) vibrational bands are a promising tool for measuring the properties of the PAH population and their effect on star formation. The photometric bands of the MIRI and NIRCam instruments on JWST provide the opportunity to measure PAH emission features across entire galaxy disks at unprecedented resolution and sensitivity. Here we present the first results of this analysis in a sample of three nearby galaxies: NGC 628, NGC 1365, and NGC 7496. Based on the variations observed in the 3.3, 7.7, and 11.3 μm features, we infer changes to the average PAH size and ionization state across the different galaxy environments. High values of F335MPAH/F1130W and low values of F1130W/F770W are measured in H ii regions in all three galaxies. This suggests that these regions are populated by hotter PAHs, and/or that the PAH ionization fraction is larger. We see additional evidence of heating and/or changes in PAH size in regions with higher molecular gas content as well as increased ionization in regions with higher Hα intensity.